Callus Induction And High Frequency Organogenesis In Saffron (Crocus Sativus L.) (Applied Biological Research, 2020)
Saffron (Crocus sativus L.) is an economically important plant with a very slow natural multiplication rate and plant tissue culture is expected to enhance its reproductive capacity. In present study, corm explants were used for micro-propagation. Auxins and cytokinin were found important for in vitro propagation of explants. Overall, 93% calli were induced from meristematic region of corm explants propagated on Murashige and Skoog (MS) medium supplemented with 2 mg L-1 2,4‐dichlorophenoxy-acetic acid (2,4-D), 0.5 mg L-1 kinetin (Kn), 2% sucrose and 100 mg L-1 ascorbic acid after 6 weeks inoculation. Somatic embryogenesis was observed on half strength MS medium supplemented with 2 mg L-1indole‐3‐acetic acid, 2 mg L-1 Kn and 100 mg L-1 ascorbic acid. Organogenesis from calli was observed with 89.6% shooting on MS medium containing 2 mg L-1 Kn and 2 mg L-1 IAA. Adventitious rooting of 91.6% calli was obtained on MS medium supplemented with 2 mg L-1indole‐3‐butyric acid. There are plenty of protocols available for tissue culture of saffron but this protocol provides an easy and time efficient method for micropropagation of saffron in vitro.
Keywords: Auxin; cytokinin; micropropagation; saffron; tissue culture